The prediction of difficult intubation with bedside scoring systems - (:unkn) unknown (My University, 2003)
Objective: The aim of this study was to evaluate the correlation of sex, age, bedside scoring systems and body mass index with laryngoscopic view in patients with clinically difficult intubation. Methods: Five hundred patients, aged 20-70 years, were included in the study. The age, sex, weight and height of the patients were recorded preoperatively and body mass index was calculated. The patients were examined for Mallampati classification, thyromental distance, mouth opening, neck mobility and structure of maxillary teeth, and scored according to airway difficulty score. The body mass index was scored as an additional parameter. During laryngoscopy, Cormack-Lehane grading was done according to the view of the glottis. Three or more attempts required for intubation and / or more than 10 minutes time spent was accepted as difficult airway. For statistical analysis; oneway of ANOVA with post-hoc Tukey and Chi-square test were used and p<0.05 was accepted as statistically significant. Results: Thirty-three of 500 patients (6.6%) had difficult intubation. A significant correlation was found between clinically difficult intubation and thyromental distance (p<0.05), Mallampati classification (p<0.01) and mouth opening (p<0.01). Also, Cormack-Lehane grading was found to be correlated with thyromental distance (p<0.05), Mallampati classification (p<0.05) and mouth opening (p<0.05). Conclusion: The difficult intubation was found to be correlated with Mallampati classification, thyromental distance and mouth opening.
Keywords: Difficult; Intubation (Intratracheal)